Identifying Individuals at High Risk for Permanent Disability From Depression and Anxiety - Behrens-Wittenberg, Eva; Wedegaertner, Felix (Frontiers in Psychiatry, 2020)
Mental illnesses, among which depression and anxiety are most common, are the leading cause for permanent disability. It is of interest to know what case characteristics determine if a person returns to the work force in spite of mental illness to tailor specific interventions. So far, there has been little research into this field. In the present study a sample of 202 workers who had permanent disability due to depression/anxiety were followed-up on. 22% started some kind of work during follow-up in a period of 30 to 75 months. Logistic regression analyses showed that quick progression into disability, short period of disability, younger age, adequacy of income replacement through insurance benefits and no previous disability predicted return to work. These findings also allow to identify individuals at high risk for progression into permanent disability that can benefit from supporting interventions.